2004
DOI: 10.1051/vetres:2004001
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bartonella infection in American free-ranging and captive pumas (Felis concolor) and bobcats (Lynx rufus)

Abstract: -Bartonella henselae is the main agent of cat scratch disease in humans and domestic cats are the main reservoir of this bacterium. We conducted a serosurvey to investigate the role of American wild felids as a potential reservoir of Bartonella species. A total of 479 samples (439 serum samples and 40 Nobuto strips) collected between 1984 and 1999 from pumas (Felis concolor) and 91 samples (58 serum samples and 33 Nobuto strips) collected from bobcats (Lynx rufus) in North America, Central America and South Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
0
19
0
5
Order By: Relevance
“…in fleas from Central America. Previous studies in Costa Rica include serologic evidence (immunoglobulin G [IgG]) of infection with Bartonella in pumas and a study in the tropical rainforest where no evidence of infection with Bartonella was detected by PCR in white-nose coatis (Chomel et al 2004, Mehrkens et al 2013. In Guatemala, Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…in fleas from Central America. Previous studies in Costa Rica include serologic evidence (immunoglobulin G [IgG]) of infection with Bartonella in pumas and a study in the tropical rainforest where no evidence of infection with Bartonella was detected by PCR in white-nose coatis (Chomel et al 2004, Mehrkens et al 2013. In Guatemala, Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Bartonella koehlerae has been isolated only from two cats in California, one cat in France and recently in one cat in Israel [8,72,196]. Furthermore, Bartonella infection has been reported in wild felids, such as pumas and bobcats in the New World [53]. Bartonella vinsonii subsp.…”
Section: Zoonotic Bartonellae With a Feline Or Canine Reservoirmentioning
confidence: 99%
“…Similarly, adults were more likely to be B. henselae –seropositive (PR = 1.77, 95% CI = 1.07, 2.93) and to have higher antibody titers ( P = 0.026) than juveniles and kittens. B. henselae antibody prevalence was 22.4% (19/85) in bobcats from the United States and 33.3% (2/6) in the Mexican bobcats 27 . Furthermore, Bartonella have been isolated from pumas and bobcats in California (Chomel et al , International Conference on Emerging Infectious Diseases, Atlanta, 1998) and shown to be infective for domestic cats 28 .…”
Section: Bartonella Henselae (B H) and B Clarridgeiae (B C) Bactmentioning
confidence: 99%